The impacts of urban air pollution on Malaysian traffic police: A framework for evaluation of real-time monitoring system on its usability - P. A. S. M., Jamil; N. A. D. M., Yusof; K., Karuppiah; I., Rasdi; V., How; S. B. M., Tamrin; K. K. C., Mani; H. S., Naeni; S., Sambasivam; D. H. M. S., Nata (Institute of Physics, 2022)
The respiratory health of Malaysian Traffic Police has been compromised by working in heavy traffic and congested junctions with bad air for long hours. A wireless outdoor individual exposure device is vital to track their exposure, however, the efficacy of the system remains uncertain. While existing techniques exist to examine the efficacy of such system, there is a lack of methodology for engaging multiple assessment methods to evaluate the degree of user experience. This paper aims to propose a methodological framework tool for a quantitative evaluation of the wireless outdoor individual exposure indicator system prototype. A systematic search was conducted in major electronic databases (MEDLINE, Web of Science, Google), grey literature sources and all relevant data in the field. A three-stage framework consisting of simulation real-time monitoring, in-field testing, and usability testing is assembled. The three-stage framework proposed serves as a generic approach for evaluating the prototype with the purpose of tracking individual outdoor exposure. The method is capable of describing the complete evaluation process, from the accuracy and performance of the sensor to the extent of the end-user experience. Using the three-stage approach, future researchers may be able to create a monitoring system that is relevant to their needs.